Relevansi Governing Law Terkait Praktek Unfair Calling pada Kontrak Jaminan Perbankan Internasional Demand Guarantee dalam Transaksi Bisnis Internasional - Denny Tendra (LPPM Universitas Ekasakti Padang, 2023)
There are two types of Bank Guarantees related to international buying and selling that are widely applicable internationally and recognized by international civil law, namely: Standby Letter of Credit (SBLC) & Demand Guarantee (DG). SBLC is a guarantee/guarantee issued by a bank, which results in the bank's obligation to pay the party receiving the confirmation (beneficiary) in the event of a default/default, or an obligation to pay from the guaranteed party (applicant). DG refers to international civil law URDG 758. The Demand Guarantee adheres to the principle of independence and the principle of document attachment, so there are two elements of risk in agreeing to the Demand Guarantee, First, namely: Disbursement of the Demand Guarantee is based only on a written claim letter from the Beneficiary to Issuing Bank. Second, namely: A clear expiration date must be stated in the Demand Guarantee. The act of claiming unilaterally by the beneficiary (the party receiving the guarantee) that the Applicant is in default even though the underlying contract conditions have been fulfilled, this is also called the practice of Unfair Calling. The URDG does not contain provisions regarding this matter. Therefore, it relies on jurisprudence and national legal laws applicable in a country (Governing Law) to determine in which case a request for disbursement of the Demand Guarantee is considered a default and unfair.